Effects of intragastrically-administered Tepary bean lectins on digestive and immune organs: Preclinical evaluation - Julia María Alatorre-Cruz (Toxicology Reports, 2018)
Previous work showed that Tepary bean (Phaseolus acutifolius) lectins exhibit differential cytotoxic effects on cancer cell lines by apoptosis induction. In vivo studies using a Tepary bean lectin fraction (TBLF, 50 mg/kg of body weight) after colon cancer induction in rats showed that TBLF inhibited early precancerous lesions without systemic toxicity however, loss of body weight gain and activation of immune cells were observed. In order to know more about the possible adverse effects, we evaluated the administration of TBLF on digestive and immune organs. Sprague Dawley rats were administered TBLF for six weeks and allowed to recover for two weeks. Immune activation was observed through an increased lymphocyte-granulocyte ratio, an increased number of lymphoid follicles in intestinal Peyer’s patches and a slight expansion of the splenic white pulp. Atrophy was observed in small intestine villi and crypt foci of the colon without normalization after the recovery period. Pancreas histopathology showed hypertrophy after the six-week administration period, particularly vacuolation and trabecular widening; but after the two-week recovery period atrophy was observed, suggesting a partial compensatory type process. Our results show that TBLF activates the immune system and affects digestive organs through direct interaction with intestinal epithelium, and indirectly by producing pancreatic hyperfunction. Further work will focus in longer recuperation periods after TBLF treatment. Keywords: Digestive tract, Immune system, Lectins, Phaseolus acutifolius, Tepary bean